Health-related quality of life outcomes from KEYNOTE-412: chemoradiotherapy with or without pembrolizumab in participants with head and neck squamous cell carcinoma - Machiels, J.-P.; Tao, Y.; Licitra, L.; Burtness, B.; Tahara, M.; Rischin, D.; Alves, G. V.; Lima, I. P. F.; Hughes, B. G. M.; Pointreau, Y.; Aksoy, S.; Laban, S.; et al. (Frontiers in Oncology, 2025)
BackgroundThe health-related quality of life (HRQoL) of patients with locally advanced head and neck squamous cell carcinoma (LA HNSCC) is impacted by both disease- and treatment-related factors. Treatments that preserve and maximize HRQoL in this setting represent a substantial unmet need.MethodsKEYNOTE-412 (NCT03040999) was a randomized, double-blind, placebo-controlled phase 3 study of pembrolizumab plus chemoradiotherapy (CRT) versus placebo plus CRT for maintenance therapy in participants with treatment-naïve LA HNSCC. Patient-reported outcomes (PROs) assessed using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) and EORTC QLQ Head and Neck 35 (H&N35) were pre-specified secondary endpoints and administered at baseline and throughout the study. Least squares mean (LSM) change from baseline was assessed using a constrained longitudinal data analysis model. No formal statistical significance testing was performed.ResultsThe PRO analysis population included 395 participants randomized to receive pembrolizumab plus CRT and 397 to receive placebo plus CRT. Completion rates for all assessed PROs were >95% at baseline and >66% at week 45. LSM change from baseline to week 45 was similar between groups across EORTC QLQ-C30 and QLQ-H&N35 subscale scores. There were no notable differences in empirical mean change or the proportion of participants with improvement, stability, or deterioration from baseline to week 45 between treatment groups.ConclusionThe addition of pembrolizumab to CRT did not meaningfully impact HRQoL in participants with LA HNSCC.